2021
DOI: 10.3389/fonc.2021.633916
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoid Adenocarcinoma of the Stomach: Current Perspectives and New Developments

Abstract: Hepatoid adenocarcinoma of the stomach (HAS) is a rare malignant tumor, accounting for only 0.17–15% of gastric cancers. Patients are often diagnosed at an advanced disease stage, and their symptoms are similar to conventional gastric cancer (CGC) without specific clinical manifestation. Morphologically, HAC has identical morphology and immunophenotype compared to hepatocellular carcinoma (HCC). This is considered to be an underestimation in diagnosis due to its rare incidence, and no consensus is reached rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 90 publications
2
54
0
Order By: Relevance
“…HAS is a rare neoplasm, and the annual incidence of HAS is approximately 0.58-0.83 cases per million people (6,15). Previous studies were mainly case reports or case series from a single medical center and mainly came from Asian regions (1,2,16). In these previous studies, HAS patients often were reported to have a worse prognosis than non-HAS patients (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAS is a rare neoplasm, and the annual incidence of HAS is approximately 0.58-0.83 cases per million people (6,15). Previous studies were mainly case reports or case series from a single medical center and mainly came from Asian regions (1,2,16). In these previous studies, HAS patients often were reported to have a worse prognosis than non-HAS patients (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatoid adenocarcinoma of the stomach (HAS) is a rare type of primary gastric cancer (GC), and most previous studies have reported that the incidence of HAS is less than 1% of all GC ( 1 , 2 ). According to the World Health Organization (WHO) gastrointestinal tumor sample classification, hepatoid adenocarcinoma (HAC) is defined as adenocarcinoma of extrahepatic origin with morphological features of liver cell differentiation, composed of large polygonal eosinophilic hepatocytes such as neoplastic cells ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatoid adenocarcinoma (HAC) is a clinically rare and specific type of malignancy that occurs in tissues and organs other than the liver (1). Histologically, the tumor cells of HAC are polygonal and proliferate in a solid or trabecular fashion, showing many hepatocellular carcinoma (HCC)-like features such as intracytoplasmic glycogen granules, centripetal annular lamellar vesicles, and proliferation in capillary bile ducts (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, the tumor cells of HAC are polygonal and proliferate in a solid or trabecular fashion, showing many hepatocellular carcinoma (HCC)-like features such as intracytoplasmic glycogen granules, centripetal annular lamellar vesicles, and proliferation in capillary bile ducts (2)(3)(4). HAC can occur in the stomach, esophagus, duodenum, jejunum, colon, peritoneum, pancreas, lungs, ovaries, gallbladder, and uterus, with the stomach being the most common site of occurrence (1,2). Hepatoid adenocarcinoma of the stomach (HAS) was first proposed in 1985 by Ishikura et al (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation